Preexcitation Syndrome with a Mahaim-type Accessory Pathway - Lee, Kwang-No; Kim, Young-Hoon (International journal of arrhythmia, 2017)
Wide QRS complex tachycardia with a left bundle branch block pattern can be caused by supraventricular tachycardia with aberrant conduction, preexcitation syndrome mediated through a right-sided accessory pathway, and/or ventricular tachycardia. The use of atrial pacing maneuvers can be beneficial for unmasking minimal preexcitation to differentiate between these conditions. Here, we report a case of successful radiofrequency catheter ablation of a Mahaim fiber in a patient with wide QRS complex tachycardia. KCI Citation Count: 0